Oxidation of Zircaloy-4 during in situ proton irradiation and corrosion in PWR primary water. Issue 9 (16th March 2015) - Wang, Peng; Was, Gary S.
Abstract: Abstract : The kinetics and morphology of oxides formed during in situ proton irradiation–corrosion experiment were analyzed. Experiments were conducted in 320 °C water with 3 wt ppm H2, while irradiated by a 3.2-MeV proton beam at a current density of 2 µA/cm 2 producing a damage rate at 4.4 × 10 −7 dpa/s. The resulting oxide was compared with reference samples corroded in an autoclave, and literature data found on in-reactor formed oxide. The corrosion rate of the sample irradiated in situ was 10 times faster than the in-pile corrosion rate. The cracked and porous irradiated oxide consisted of monoclinic equiaxed grains of zirconia with a preferential orientation of the oxide grains. Second phase particles (SPPs) consumed by the oxidation front were rapidly oxidized, but no SPPs were amorphized or dissolved in the metal matrix of the irradiated sample.